Analysis of three-dimensional knee kinematics during stair descent two decades post-ACL rupture – Data revisited using statistical parametric mapping. (February 2017) - Sole, Gisela; Pataky, Todd; Tengman, Eva; Häger, Charlotte
Abstract: Changes in movement patterns following knee injuries have generally used analyses of pre-defined discrete event-related variables, whereas Statistical Parametric Mapping (SPM) assesses continuous data over time. We applied SPM to test differences for knee trajectories during stair descent between participants with past anterior cruciate ligament (ACL) rupture who underwent reconstruction or only physical therapy compared to healthy controls. Three-dimensional knee joint kinematics during stair descent were registered for 31 subjects with ACL reconstruction (ACLR ), 36 subjects with ACL rupture managed with physical therapy only (ACLPT ) (∼23 years post-injury), and 32 uninjured controls. SPM was used to assess differences between groups for the entire three-component knee trajectory. A significant difference between the three groups was found for the first ∼10% of stance phase. Post-hoc analyses showed between-group differences when comparing the ACLPT to the control groups. Analyses of ACLPT versus control groups for individual vector components suggested a combination of less flexion at initial foot contact, and less adduction during weight acceptance (∼40% of stance). Altered knee kinematics were confirmed during weight acceptance of stair descent for the ACLPT group compared to controls, but not for ACLR group. Further exploration of the use of SPM and agreement with clinical gait assessment is warranted.